‘To Have Your Cake and Eat It Too?’ Utility, Ecology, Equity and Québec’s New Forest Act, 2001 - Houde, Nicolas; Sandberg, Anders (Cahiers de géographie du Québec)

(untitled) (Département de géographie, 2003)
AbstractThe new Québec Forest Act appears to give the provincial government a stronger position as umpire in the forest sector. A policy community interpretation suggests that the government has created a mechanism for more input from other stakeholders than the traditional powerhouse, the forest industry, and that progress is being made towards a more socially and ecologically sustainable form of forestry.Yet a closer examination of the new Forest Act reveals a more uncertain situation. When exploring the outcome of the Forest Act thus far it can be argued that it has not challenged the dominant position of an “economic development” coalition. The dominance of this coalition is reflected in the increasing control of forest lands in fewer hands. There is also evidence that public participation serves as a vehicle for the forest industry and the government to feed the public “information” without taking into account other participants’ views. An environmental coalition has made some gains, but the promotion of increased forest yield may compromise the protection of the forest environment. An autonomous or First Nations development coalition has also made some gains, though these are principally confined to the northern Cree and leave most other groups unaffected.